The Effect of E-Word of Mouth (E-WOM) on Various Factors Influencing Customers’ Hotel Booking Intention - Kitcharoen, Krisana (ABAC ODI JOURNAL Vision. Action. Outcome, 2019)
Electronic word of mouth received by customers would lead to their hotel booking intention via smartphones both on online or mobile phone application such as Agoda or Booking.com. Travelers who read comments or reviews and made a hotel choice based on those comments were targeted for this study. The research aims to determine the effect of electronic word of mouth on factors influencing hotel booking intention via smartphones. The research hypotheses determine the effect electronic word of mouth attributed toward perceived behavioral control (PB), perceived benefits (PB), subjective norm (SN) and attitude (AT) and how they influence hotel booking intention via smartphones. The paper examines the difference between genders and the purposed model was empirically tested using data collected from an online channel with total respondent of 400 who live in Bangkok. Simple linear regression, multiple linear regression and independent sample T-Test were used for data analysis . This means that travelers want to be known about both complaints and compliments in the online comments. However, this does not mean they intend to reserve a hotel room based on both opinions rather travelers would be approached to reserve a hotel room based on comments. Moreover, this research will help hotel investors, as well as online travel agency operators, to obtain a clearer understanding of guests’ needs and wants in order to offer a more desirable service.